Radiocarbon and OSL dating on cores from the Chaoshan delta in the coastal South China Sea - Zhong, Jiemei; Ling, Ken; Yang, Meifei; Shen, Qinjing; Abbas, Mahmoud; Lai, Zhongping (Frontiers in Marine Science, 2022)
Accurate chronology plays a crucial role in reconstructing delta evolution. Radiocarbon (14C) and optically stimulated luminescence (OSL) dating are widely used to establish a stratigraphic chronology of the late Quaternary sediments. The Chaoshan plain is located on the southern coast of China and borders the South China Sea. The thickness of Quaternary sediments in this area extends to a depth of 140 m and is considered a valuable archive for studying the evolution of the delta in response to climate and sea-level changes. However, reliable chronological data are still very limited. In this paper, eighteen accelerator mass spectrometry (AMS) 14C and thirteen quartz OSL ages were obtained from two cores from the Rongjiang plain, the middle part of the Chaoshan plain: ZK001 (90.85 m in depth) and ZK002 (100 m in depth). The present study aims to provide a reliable chronology of the Chaoshan plain based on OSL and 14C dating methods and examine the upper limit of the 14C dating on plant remains. Our results show that (1) OSL ages of cores ZK001 and ZK002 range from 56 to 1.7 ka and from 177 to 15 ka, respectively; (2) 14C ages of core ZK002 range from 8.8 to 41 cal ka BP, showing that all 14C ages below ca. 30 m depth are younger than OSL ages and that the upper limit of plant remains is around 35 cal ka BP. OSL ages are consistent with stratigraphic order within uncertainties. The oldest OSL age obtained from core ZK002 is 177 ± 20 ka at a depth of 93 m, and is considered a minimum age. This indicates that the Quaternary deposition in the Rongjiang plain can trace back to at least the marine isotope stage (MIS) 6 during sea-level lowstand, during which the plain is mainly influenced by the fluvial process. The comparison between 14C and OSL ages in the Chaoshan plain suggests that 14C ages older than 35 cal ka BP need to be re-evaluated. However, the OSL dating method proves reliable for establishing a comprehensive chronological framework for the late Quaternary sediments in this area.